AuNP/Magnetic Bead-Enhanced Electrochemical Sensor Toward Dual Saliva Alzheimer’s Biomarkers Detection - Pengcheng Zhao; Jieyu Wang; Hongju Mao; Lin Zhou; Zhenhua Wu; Yunxing Lu; Teng Sun; Jianan Hui; Guowu Ma (Sensors)
Alzheimer’s disease (AD) early screening requires non-invasive, high-sensitivity detection of low-abundance biomarkers in complex biofluids like saliva. In this study, we present a miniaturized, silicon-based electrochemical sensor for sequential detection of two AD salivary biomarkers, lactoferrin (Lf) and amyloid β-protein 1-42 (Aβ1-42), on a single reusable electrode. The sensor features a three-electrode system fabricated by sputter-coating a quartz substrate with gold (Au) sensing electrodes, which are further modified with gold nanoparticles (AuNPs) to form 3D dendritic structures that enhance surface area and electron transfer. To improve specificity, immunomagnetic beads (MBs) are employed to selectively capture and isolate target biomarkers from saliva samples. These MB–biomarker complexes are introduced into a polydimethylsiloxane chamber aligned with Au sensing electrodes, where a detachable magnet localizes the complexes onto the electrode surface to amplify redox signals. The AuNPs/MBs sensor achieves detection limits of 2 μg/mL for Lf and 0.1 pg/mL for Aβ1-42, outperforming commercial ELISA kits (37.5 pg/mL for Aβ1-42) and covering physiological salivary concentrations. After the MBs capture the biomarkers, the sensor can output the result within one minute. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) measurements confirm enhanced electron transfer kinetics on AuNP-decorated surfaces, while linear correlations (R2 > 0.95) validate quantitative accuracy across biomarker ranges. The compact and integrated design eliminates reliance on bulky instrumentation and enables user-friendly operation, establishing a promising platform for portable, cost-effective AD screening and monitoring.